2018
DOI: 10.1159/000489595
|View full text |Cite
|
Sign up to set email alerts
|

MiR-27b Promotes Muscle Development by Inhibiting MDFI Expression

Abstract: Background/Aims: Skeletal muscle plays an essential role in the body movement. However, injuries to the skeletal muscle are common. Lifelong maintenance of skeletal muscle function largely depends on preserving the regenerative capacity of muscle. Muscle satellite cells proliferation, differentiation, and myoblast fusion play an important role in muscle regeneration after injury. Therefore, understanding of the mechanisms associated with muscle development during muscle regeneration is essential for devising t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…MDFI was enriched in "negative regulation of WNT signaling pathway". High expression of MDFI inhibits porcine muscle satellite cell proliferation and promotes their differentiation [39]. ASPN was enriched in "anatomic structure development".…”
Section: Discussionmentioning
confidence: 99%
“…MDFI was enriched in "negative regulation of WNT signaling pathway". High expression of MDFI inhibits porcine muscle satellite cell proliferation and promotes their differentiation [39]. ASPN was enriched in "anatomic structure development".…”
Section: Discussionmentioning
confidence: 99%
“…An additional regulatory feedback loop involving miRNAs in promoting satellite cells differentiation has been demonstrated to reduce MyoD family inhibitor (MDFI) expression. miR-27b has been shown to inhibit the proliferation of pig satellite cells and to promote their differentiation in vitro, through the suppression of MDFI [82]. MDFI hides the nuclear localization signal of MyoD family protein, leading to the accumulation of transcription factors in the cytoplasm.…”
Section: Mirnas Role In Myogenesismentioning
confidence: 99%
“…Zhang et al [13] found miR-143 promoted the differentiation of bovine SMSCs by targeting IGFBP5. miR-27b was identified as an activator of differentiation but an inhibitor of proliferation by targeting MDFI in porcine pig satellite cells [14]. Miao et al [15] proved that miR-194 functioned as a suppressor of the proliferation and migration of osteosarcoma cells.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%